Polymer Light Emitting Devices: High‐Speed OLEDs and Area‐Emitting Light‐Emitting Transistors from a Tetracyclic Lactim Semiconducting Polymer (Advanced Optical Materials 21/2018). Issue 21 (5th November 2018) - Ahmad, Viqar; Shukla, Atul; Sobus, Jan; Sharma, Anirudh; Gedefaw, Desta; Andersson, Gunther G.; Andersson, Mats R.; Lo, Shih‐Chun; Namdas, Ebinazar B.
Abstract : In article number1800768, Ebinazar B. Namdas and co‐workers report high‐speed organic light emitting diodes (OLEDs) and area emitting light‐emitting transistors using a tetracyclic lactam polymer. The fabricated devices exhibit an extremely high electroluminescence switching frequency of around 40 MHz at ultra‐short pulse widths of 10 ns. This work provides the device physics and an OLED comparison with other polymers along with ultraviolet photon spectroscopy, inversed photoelectron spectroscopy and photo‐physical measurements of the polymer.